Erythrocytes and their role as health indicator: Using structure in a patient-orientated precision medicine approach. Issue 4 (July 2016) - Pretorius, Etheresia; Olumuyiwa-Akeredolu, Oore-ofe O.; Mbotwe, Sthembile; Bester, Janette
Abstract: The relevance of erythrocyte light microscopy analysis (a well-known haematological method) is under the spotlight, however there is a place for innovative electron microscopy, (together with biochemical markers) in a pathology laboratory. Inflammation is a key indicator of the health status and erythrocytes are extremely sensitive to oxidative stress or cytokine upregulation, which typically accompany systemic inflammation in most diseases. They are probably the most adaptable cells, and due to their short lifespan, may form a vital indicator of health, and could play a central part in tracking disease and treatment. As the NIH is proposing a precision medicine approach and because individualised medicine should form an essential part in diagnosis and treatment, biophysical combined with biochemical analysis of erythrocytes may be a novel method to track the inflammatory status before and after treatment. This will allow a fully individualised patient orientated precision medicine approach, where one-medication-regime-fits-all is no longer appropriate.